ASSESSMENT OF CYTOGENOTOXICITY INDUCED BY LEAD ACETATE ON ROOT TIP CELLS OF ONION (Allium cepa L.) (Applied Biological Research, 2023)
The aim of present study was to assess the cytotoxic and genotoxic potency  of lead acetate using an Allium root tip bioassay. Root tips of Allium cepa  L. were treated with different concentrations of lead acetate viz., 0.03, 0.06,  and 0.09 mg mL-1 of lead acetate for 48 h. Mitotic index (MI), phase index  (PI), and total chromosomal abnormalities (TA) were calculated. The  effect of lead acetate was found to be dose-dependent. The frequency of MI  ranged from 8.4 to 5.7%, PI of prophase from 4.2 to 3.4%, PI of  metaphase from 1.14 to 1.11%, PI of anaphase from 1.8 to 0.6%, and PI of  telophase from 1.1 to 0.4%. The total chromosomal abnormality (TA)  ranged from 0.42 to 1.39%. The differences between the averages of all the  studied properties were significantly affected by the heavy metal lead  acetate concentration variant applied. Mitotic observation showed that  increasing of concentration variants doses decrease mitotic index and  increased chromosomal abnormality percentage. Various types of  physiological and clastogenic (laggard, stickiness, abnormal metaphase,  chromatin bridge, and delayed anaphase were observed in Allium cepa root tip cells. Moreover, the A. cepa root tibioassay method gives critical  data for evaluating an agent's action mechanisms and impacts on genetic  material.
Keywords: Abnormalities; Allium cepa; genotoxicity; lead acetate; mitotic index